Cutaneous leishmaniasis - Ahmed, Zakir; Chowdhury, SA; Bhuiyan, SI (Mymensingh Medical Journal, 2009)
Mymensingh Med J. 2009 Jul;18(2):260-3. The abstract of this article is available on the PubMed website